1997
DOI: 10.1128/jvi.71.12.9075-9086.1997
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the human immunodeficiency virus type 1 Pol protein and the primer binding site in the placement of primer tRNA(3Lys) onto viral genomic RNA

Abstract: Factors that modulate the placement of primer tRNA(3Lys) onto the viral RNA genome in human immunodeficiency virus type 1 (HIV-1) were investigated through analysis of reverse-transcribed products that are extended from the tRNA(3Lys) primer. Mutations were introduced into the HIV-1 pol gene to result in the appearance of a stop codon in the open reading frame of the reverse transcriptase (RT) gene. These constructs, BH10-RT1 and BH10-RT2, yielded viruses with truncated Pol proteins. Alternatively, we altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, several observations seem to argue against this possibility. First, an early study suggested that tRNA annealing was incomplete in newly released particles of avian leukosis virus (9), and secondly, a recent report indicated that the placement was also incomplete in immature (PR-deficient) HIV-1 particles (28). The fact that the annealing is not complete at the moment of virus release suggests that it occurs simultaneously with virus assembly; perhaps under normal circumstances it is catalyzed in part by the Gag polyprotein and in part by NC.…”
Section: Fig 5 Placement Of Trnamentioning
confidence: 99%
“…However, several observations seem to argue against this possibility. First, an early study suggested that tRNA annealing was incomplete in newly released particles of avian leukosis virus (9), and secondly, a recent report indicated that the placement was also incomplete in immature (PR-deficient) HIV-1 particles (28). The fact that the annealing is not complete at the moment of virus release suggests that it occurs simultaneously with virus assembly; perhaps under normal circumstances it is catalyzed in part by the Gag polyprotein and in part by NC.…”
Section: Fig 5 Placement Of Trnamentioning
confidence: 99%
“…These PBS mutations, for example, M1, M2, M3, and M4 in this study, do not markedly affect HIV-1 infection of SupT1 cells, likely because viral reverse transcriptase is able to tolerate the minimal mismatch between viral RNA and tRNA 3 Lys and start reverse transcription. In theory, PBS mutations should be quickly lost in HIV-1 replication due to the regeneration of the wild-type PBS sequence by copying the first 18 nucleotides of cellular tRNA 3 Lys (32)(33)(34)(35). However, our study shows that HIV-1 takes advantage of several mechanisms to maintain these escape mutations in PBS and achieve wild-type-like replication in SupT1 cells that express Cas9 and sgPBS1 or sgPBS2.…”
Section: Discussionmentioning
confidence: 77%
“…Given that each replication cycle of HIV-1 regenerates the wild-type PBS sequence by copying cellular tRNA 3 Lys , we expected that, during long-term replication of the M1 and M2 mutants in control SupT1 cells, the wild-type PBS viruses would become the prevalent viral population in the absence of the selection pressure of sgPBS1. This mechanism has been reported for various PBS mutations that revert to the wild-type sequence after prolonged replication (32)(33)(34)(35). We thus sequenced the viruses that were harvested at the peak of long-term replication of M1 and M2 viruses in control SupT1 cells.…”
mentioning
confidence: 80%